1990
DOI: 10.1002/cne.902960402
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cfos‐like protein as a marker for neuronal activity following noxious stimulation in the rat

Abstract: C-fos is a proto-oncogene that is expressed within some neurons following depolarization. The protein product, c-fos protein, can be identified by immunohistochemical techniques. Therefore, c-fos expression might be used as a marker for neuronal activity throughout the neuraxis following peripheral stimulation. This study has analyzed patterns of c-fos expression in both control and anesthetized animals and in anesthetized rats subjected to various forms of peripheral stimulation. Labeled cells were counted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
435
7
18

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 977 publications
(502 citation statements)
references
References 50 publications
31
435
7
18
Order By: Relevance
“…We previously have found that injections in the absence of light isoflurane impairs maternal aggression (S.C. Gammie, unpublished observations), but injections with light isoflurane could also have a minor negative impact. Previous studies have demonstrated that slight stimuli like injections (Asanuma et al, 1992;Asanuma and Ogawa, 1994;Morgan et al, 1987;Nakajima et al, 1989;Ryabinin et al, 1999;Sharp et al, 1991), anesthesia (Bullitt, 1990;Dragunow et al, 1990;Morgan et al, 1987), and handling ( Asanuma et al, 1992;Asanuma and Ogawa, 1994;Ryabinin et al, 1999) can induce c-Fos mRNA or protein in the male rodent brain. The c-Fos-IR in behaviorally-naïve mice supports the idea that injection with isoflurane itself is a stressor.…”
Section: Discussionmentioning
confidence: 99%
“…We previously have found that injections in the absence of light isoflurane impairs maternal aggression (S.C. Gammie, unpublished observations), but injections with light isoflurane could also have a minor negative impact. Previous studies have demonstrated that slight stimuli like injections (Asanuma et al, 1992;Asanuma and Ogawa, 1994;Morgan et al, 1987;Nakajima et al, 1989;Ryabinin et al, 1999;Sharp et al, 1991), anesthesia (Bullitt, 1990;Dragunow et al, 1990;Morgan et al, 1987), and handling ( Asanuma et al, 1992;Asanuma and Ogawa, 1994;Ryabinin et al, 1999) can induce c-Fos mRNA or protein in the male rodent brain. The c-Fos-IR in behaviorally-naïve mice supports the idea that injection with isoflurane itself is a stressor.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we saw that the sham surgical procedure altered acute noxious stimulation-induced c-Fos expression in certain regions of the antBST (increased in OV and decreased in FU). It is unclear how these modifications in c-Fos expression alter antBST activity, however, given the strong correlation between noxious stimuli-induced c-Fos expression and neuronal activation, at least in the dorsal horn of the spinal cord, the most plausible hypothesis is that the change in c-Fos expression is due to modifications in neuronal responding, habituation or sensitization in the BST (Bullitt, 1990;Coggeshall, 2005). Alternatively, noxious information from the periphery to the BST might be modified after chronic pain or sham surgery.…”
Section: Noxious Stimulation-induced Neuronal Activation In the Bstmentioning
confidence: 99%
“…Alteration in signaling pathways leading to c-Fos expression could have also affected c-Fos immunoreactivity. There is, however, little evidence from the literature suggesting alterations in the signaling pathways leading to c-Fos protein expression whereas abundant evidence supports underlying modifications in neuronal activity with associated changes in behaviours (Bullitt, 1990;Coggeshall, 2005). It is unclear why the pain-induced c-Fos-IR was blunted in the FU in both CCI and shams animals, although both inflammation and simple surgical incisions alter c-Fos expression in the spinal cord (Prewitt and Herman, 1998).…”
Section: Noxious Stimulation-induced Neuronal Activation In the Bstmentioning
confidence: 99%
“…Finally, since nocifensive reflex enhancement by pentobarbital is nitric oxide-(NO) dependent, 7 we examined the lumbar spinal cords of stimulated animals for evidence of induction of the immediate-early-gene (IEG), c-fos in the spinal cord, which is proposed to be a marker for Nmethyl-D-aspartate (NMDA) receptor-mediated, NOdependent spinal cord plasticity. [8][9][10] Here we show that despite repeated stimulation during hyperreflexia induced by pentobarbital 30 mg·kg -1 , rats showed no behavioural, reflexive, or histochemical signs of longlasting changes in nociceptive transmission.…”
Section: Discussionmentioning
confidence: 52%